Westonci.ca is the ultimate Q&A platform, offering detailed and reliable answers from a knowledgeable community. Our platform provides a seamless experience for finding reliable answers from a knowledgeable network of professionals. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.
Sagot :
Absolutely! Let's tackle the problem step-by-step.
### Part 1: Converting [tex]\(1.5454\ldots\)[/tex] to a fraction
First, let's express the repeating decimal [tex]\(1.5454\ldots = 1.\overline{54}\)[/tex] in the form [tex]\(\frac{p}{q}\)[/tex].
1. Let [tex]\( x = 1.\overline{54} \)[/tex].
2. To eliminate the repeating part, we multiply [tex]\( x \)[/tex] by 100 (because the repeating block "54" has two digits).
[tex]\[ 100x = 154.\overline{54} \][/tex]
3. Subtract the original [tex]\( x \)[/tex] from this equation:
[tex]\[ 100x - x = 154.\overline{54} - 1.\overline{54} \][/tex]
This simplifies to:
[tex]\[ 99x = 153 \][/tex]
4. Solve for [tex]\( x \)[/tex]:
[tex]\[ x = \frac{153}{99} \][/tex]
5. Simplify the fraction [tex]\(\frac{153}{99}\)[/tex]. The greatest common divisor (GCD) of 153 and 99 is 9. Dividing both the numerator and the denominator by 9 gives:
[tex]\[ \frac{153 \div 9}{99 \div 9} = \frac{17}{11} \][/tex]
Therefore, [tex]\( 1.\overline{54} = \frac{17}{11} \)[/tex].
### Part 2(a): Simplify [tex]\((3\sqrt{2} - 2\sqrt{3})^2\)[/tex]
Here, we expand and simplify the expression using the binomial theorem:
1. Start with the square:
[tex]\[ (3\sqrt{2} - 2\sqrt{3})^2 = (3\sqrt{2})^2 - 2 \cdot 3\sqrt{2} \cdot 2\sqrt{3} + (2\sqrt{3})^2 \][/tex]
2. Simplify each term:
[tex]\[ (3\sqrt{2})^2 = 9 \cdot 2 = 18 \][/tex]
[tex]\[ 2 \cdot 3\sqrt{2} \cdot 2\sqrt{3} = 2 \cdot 3 \cdot 2 \cdot \sqrt{2} \cdot \sqrt{3} = 12 \sqrt{6} \][/tex]
[tex]\[ (2\sqrt{3})^2 = 4 \cdot 3 = 12 \][/tex]
3. Combine the terms:
[tex]\[ 18 - 12\sqrt{6} + 12 \][/tex]
4. Summarize:
[tex]\[ 18 + 12 - 12\sqrt{6} = 30 - 12\sqrt{6} \][/tex]
Therefore, [tex]\((3\sqrt{2} - 2\sqrt{3})^2 = 30 - 12\sqrt{6}\)[/tex].
### Part 2(b): Simplify [tex]\((5 + \sqrt{5})(5 - \sqrt{5})\)[/tex]
Here, we recognize the difference of squares:
1. Use the formula [tex]\( (a + b)(a - b) = a^2 - b^2 \)[/tex]:
[tex]\[ (5 + \sqrt{5})(5 - \sqrt{5}) = 5^2 - (\sqrt{5})^2 \][/tex]
2. Simplify each term:
[tex]\[ 5^2 = 25 \][/tex]
[tex]\[ (\sqrt{5})^2 = 5 \][/tex]
3. Subtract:
[tex]\[ 25 - 5 = 20 \][/tex]
Therefore, [tex]\((5 + \sqrt{5})(5 - \sqrt{5}) = 20\)[/tex].
### Summary of Solutions
1. [tex]\(1.\overline{54} = \frac{17}{11}\)[/tex]
2. [tex]\((3\sqrt{2} - 2\sqrt{3})^2 = 30 - 12\sqrt{6}\)[/tex]
3. [tex]\((5 + \sqrt{5})(5 - \sqrt{5}) = 20\)[/tex]
These are the simplified results of the given mathematical expressions.
### Part 1: Converting [tex]\(1.5454\ldots\)[/tex] to a fraction
First, let's express the repeating decimal [tex]\(1.5454\ldots = 1.\overline{54}\)[/tex] in the form [tex]\(\frac{p}{q}\)[/tex].
1. Let [tex]\( x = 1.\overline{54} \)[/tex].
2. To eliminate the repeating part, we multiply [tex]\( x \)[/tex] by 100 (because the repeating block "54" has two digits).
[tex]\[ 100x = 154.\overline{54} \][/tex]
3. Subtract the original [tex]\( x \)[/tex] from this equation:
[tex]\[ 100x - x = 154.\overline{54} - 1.\overline{54} \][/tex]
This simplifies to:
[tex]\[ 99x = 153 \][/tex]
4. Solve for [tex]\( x \)[/tex]:
[tex]\[ x = \frac{153}{99} \][/tex]
5. Simplify the fraction [tex]\(\frac{153}{99}\)[/tex]. The greatest common divisor (GCD) of 153 and 99 is 9. Dividing both the numerator and the denominator by 9 gives:
[tex]\[ \frac{153 \div 9}{99 \div 9} = \frac{17}{11} \][/tex]
Therefore, [tex]\( 1.\overline{54} = \frac{17}{11} \)[/tex].
### Part 2(a): Simplify [tex]\((3\sqrt{2} - 2\sqrt{3})^2\)[/tex]
Here, we expand and simplify the expression using the binomial theorem:
1. Start with the square:
[tex]\[ (3\sqrt{2} - 2\sqrt{3})^2 = (3\sqrt{2})^2 - 2 \cdot 3\sqrt{2} \cdot 2\sqrt{3} + (2\sqrt{3})^2 \][/tex]
2. Simplify each term:
[tex]\[ (3\sqrt{2})^2 = 9 \cdot 2 = 18 \][/tex]
[tex]\[ 2 \cdot 3\sqrt{2} \cdot 2\sqrt{3} = 2 \cdot 3 \cdot 2 \cdot \sqrt{2} \cdot \sqrt{3} = 12 \sqrt{6} \][/tex]
[tex]\[ (2\sqrt{3})^2 = 4 \cdot 3 = 12 \][/tex]
3. Combine the terms:
[tex]\[ 18 - 12\sqrt{6} + 12 \][/tex]
4. Summarize:
[tex]\[ 18 + 12 - 12\sqrt{6} = 30 - 12\sqrt{6} \][/tex]
Therefore, [tex]\((3\sqrt{2} - 2\sqrt{3})^2 = 30 - 12\sqrt{6}\)[/tex].
### Part 2(b): Simplify [tex]\((5 + \sqrt{5})(5 - \sqrt{5})\)[/tex]
Here, we recognize the difference of squares:
1. Use the formula [tex]\( (a + b)(a - b) = a^2 - b^2 \)[/tex]:
[tex]\[ (5 + \sqrt{5})(5 - \sqrt{5}) = 5^2 - (\sqrt{5})^2 \][/tex]
2. Simplify each term:
[tex]\[ 5^2 = 25 \][/tex]
[tex]\[ (\sqrt{5})^2 = 5 \][/tex]
3. Subtract:
[tex]\[ 25 - 5 = 20 \][/tex]
Therefore, [tex]\((5 + \sqrt{5})(5 - \sqrt{5}) = 20\)[/tex].
### Summary of Solutions
1. [tex]\(1.\overline{54} = \frac{17}{11}\)[/tex]
2. [tex]\((3\sqrt{2} - 2\sqrt{3})^2 = 30 - 12\sqrt{6}\)[/tex]
3. [tex]\((5 + \sqrt{5})(5 - \sqrt{5}) = 20\)[/tex]
These are the simplified results of the given mathematical expressions.
We appreciate your visit. Hopefully, the answers you found were beneficial. Don't hesitate to come back for more information. Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Stay curious and keep coming back to Westonci.ca for answers to all your burning questions.